EDUCAȚIA UNIVERSITARĂ INCLUZIVĂ ÎN COMUNITĂȚILE ACADEMICE VOCAȚIONALE CU REFERIRE SPECIFICĂ LA INSTITUTUL TEOLOGIC BAPTIST DIN BUCUREȘTI (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2023)
Inclusive University Education in Vocational Academic Communities With Particular Reference to the Baptist Theological Institute in Bucharest.The contemporary academic arena is making more and more space for disabled persons, as we aim to develop a society based on equity and solidarity. However, is it possible for the vocational academic communities to adopt an inclusive approach? Or should we better say that vocational training is out of reach for disabled people? Our answer, as we shall argue in this paper, is that vocational universities can be inclusive, and they are suitable for all persons. We make a particular reference to the Baptist Theological Institute in Bucharest, to emphasize how different measures such as accessibility of various campus facilities as well as accessibility of academic content can open vocational training for disabled students. Digital education and proper educational and psychological counselling are great tools towards reaching this goal.